“Without regard to race”: Critical ideational development in modern American politics - King, D; Smith, R (University of Chicago Press, 2014)
Many scholars note that racial policy issues now focus on color-blind versus race-conscious approaches to racial inequalities, but they have not adequately explained how this development occurred or its consequences. Using work theorizing the role of ideas in politics, this article argues that these changes represent a “critical ideational development.” Diverse strains in earlier racial policy positions were reformulated to advance not just old racial goals but new ones. This critical ideational development produced advantages for conservative coalition building and Republican electoral campaigns, thereby contributing to the Reagan Revolution and later polarization and gridlock, and it helped drive racial issues out of campaigns and into other venues, especially legislative, administrative, and judicial hearings. It has not been associated with great progress in reducing racial inequalities or promoting racial harmony